Indigenous and African diaspora religions in the Americas - Hebblethwaite, Benjamin; Jansen, Silke (University of Nebraska Press, 2023)
Indigenous and African Diaspora Religions in the Americas offers an introduction and nine original perspectives on religious and cultural traditions emanating from communities in several regions across the Americas.